Metabolomic Understanding of variable risk factors for kidney cancer: a two-sample Mendelian randomization study - Yihao Zhu; Ke Wang; Yuan Yu; Xuwen Li; Yabo Zhai; Can Chen; Yajian Li; Mingshuai Wang; Dong Chen; Nianzeng Xing; Feiya Yang; Xiongjun Ye (Discover Oncology)
Abstract Background Circulating metabolites have been found to play an important role in the development of renal cancer, however, the specific pathways and mechanisms of their influence are still largely unknown. We aimed to investigate the role of metabolites in kidney cancer development and to explain the development of kidney cancer from a genetic perspective. Method We explored the role of plasma metabolites and urinary metabolites in kidney cancer using two-sample mendelian randomization (MR) separately and validated it using multiple databases; in addition, we performed rigorous tests of pleiotropy and heterogeneity to ensure that the results were robust. Next, we explored the role of common modifiable risk factors in kidney cancer and identified the specific mechanisms by which risk factors affect kidney cancer by joint analysis of TCGA and GEO databases. Results Through MR analysis, we identified six plasma metabolites and one urinary metabolite that play a major role in kidney cancer, confirmed the effects of BMI and type 1 diabetes mellitus on kidney cancer, and constructed the BMI-plasma metabolite-kidney cancer causality networks through mediated MR. In addition, we found that SLPI could significantly affect the prognosis of kidney cancer through multiple databases’ joint analyses, and through multiple methods explored the pathways of SLPI’s influence on kidney cancer. Conclusions In a word, this study shows that BMI can significantly increase the risk of kidney cancer, while the plasma metabolites 4-guanidinobutanoate may partially mitigate this risk, and that SLPI promotes tumorigenesis in obesity-related renal cancer by regulating protease activity.